Laurie Booth Review from the Festival's Anniversary Season - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review from the Dance Umbrella Festival's Anniversary Season. PALABRAS CLAVE: Laurie Booth, Ice/Dreams/Fire.
Dentro del apartado "Silver Jubilee: Dance Umbrella at 25".